2017
DOI: 10.1515/cdbme-2017-0007
|View full text |Cite
|
Sign up to set email alerts
|

Compensating the effects of FES-induced muscle fatigue by rehabilitation robotics during arm weight support

Abstract: Abstract:Motor functions can be hindered in consequence to a stroke or a spinal cord injury. This often results in partial paralyses of the upper limb. The effectiveness of rehabilitation therapy can be improved by the use of rehabilitation robotics and Functional Electrical Stimulation (FES). We consider a hybrid arm weight support combining both. In order to compensate the effect of FES-induced muscle fatigue, we introduce a method to substitute the decreasing level of FES support by cable-driven robotics. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…It is recognized that several research groups discuss the integration of FES with robotic arms with passive actuators. In their research, Meyer-Rachner et al [31] developed a computerized system using a rope as an arm support, shown in the schematic representation in Figure 5A. Rope support is applied to robotics to support the gravitational force of the arm with an adjusted rope load calculated using a static arm model in a hanging position and moving horizontally to achieve a forearm posture.…”
Section: Integration Of Fes and Robot Arm With Passive Actuatorsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is recognized that several research groups discuss the integration of FES with robotic arms with passive actuators. In their research, Meyer-Rachner et al [31] developed a computerized system using a rope as an arm support, shown in the schematic representation in Figure 5A. Rope support is applied to robotics to support the gravitational force of the arm with an adjusted rope load calculated using a static arm model in a hanging position and moving horizontally to achieve a forearm posture.…”
Section: Integration Of Fes and Robot Arm With Passive Actuatorsmentioning
confidence: 99%
“…Meyer-Rachner et al [31] in their research, they reported the results of using two straps as actuators of a robotic system mounted on the elbow, forearm, and wrist joints integrated with FES. The evaluation of the trial was carried out with one healthy subject doing repetitive lifting of the arm, the EMG was recorded and processed to obtain signals of FES-induced muscle activity.…”
Section: Hybrid Robotic Outcome Scale Based On a Passive Actuator Exo...mentioning
confidence: 99%
See 1 more Smart Citation
“…In particular in stroke rehabilitation, the effects of muscular fatigue have been explored in patients with post-stroke spasticity which present abnormal antagonistic muscle co-activation patterns, because there exist a significant influence of muscle fatigue on the coupling of antagonistic muscles (Wang L.-J. et al, 2020) Comment on current/potential applications: The exploration of potential adaptive robotic system for rehabilitation using muscle fatigue as a trigger has been tested for improve engagement and performance (Meyer-Rachner et al, 2017;Mugnosso et al, 2018;Huang et al, 2019;Kanal et al, 2019). Novel methods for fatigue detection are continuously being developed, boosted by machine learning algorithms and wearables EMG sensors (Mugnosso et al, 2017;Papakostas et al, 2019;Wang W. et al, 2020;Liu et al, 2021) 6.…”
Section: Muscle Fatiguementioning
confidence: 99%